Perancangan Aplikasi Agenda Kegiatan Guru Berbasis Website - Setiawan, Ito; Waluyo, Retno; Suseno, Wahyu (Infotekmesin, 2022)
Impact of COVID-19 is very influential in various fields, one of which is the field of education with online learning through government regulations. The implementation of the learning from home policy will be implemented starting in mid-March 2020. With home learning, a teacher is still required to administer the daily agenda of learning activities. Currently the teacher's daily agenda is still in the form of books, with learning from home this makes it increasingly difficult for principals to check and supervise learning activities carried out by teachers, homeroom supervision of students is increasingly difficult. So there needs to be a breakthrough in the online learning process, one of which is through the website. The purpose of this research is to design a website-based teacher activity agenda information system. the system development method used is the System Development Life Cycle (SDLC) method with the waterfall model. the results of this study have created a web-based teacher activity agenda information system, after the Alpha test with the blackbox method got the results that the existing features were running well in accordance with their functions